The role and pharmacological characteristics of ATP-gated ionotropic receptor P2X in cancer pain. (November 2020) - Zhang, Wen-jun; Luo, Chen; Pu, Fan-qin; Zhu, Jing-feng; Zhu, Zhengming
Graphical abstract: Abstract: Many factors are involved in the development of cancer pain, which is a serious complication of cancer and affects the quality of life of patients, Normally, drugs are used to relieve pain in clinic, but the effect is not satisfactory to patients. Therefore, it is necessary to explore the molecular basis of the pathogenesis of cancer pain and carry out targeted therapy. Fortunately, the important role of P2X purine receptors dependent on ATP ion channels in the development of cancer pain has been recognized. In the development of cancer, ATP concentration in the tumor microenvironment is high enough to activate P2X purine receptors, sensitive peripheral receptors, enhance sensory nerve fiber information transmission, sensitize the central nervous system, and induce or aggravate pain. Here, we outlined the role of P2X purine receptors in the development of cancer, and discussed the intrinsic correlation between P2X purine receptors and cancer pain. Moreover, we also explored the pharmacological properties of P2X antagonists or inhibitors to inhibit cancer pain, and hope to provide some value for the treatment of cancer pain in the future. In short, up-regulation of P2X expression can induce or aggravate cancer pain, while reducing P2X expression level can inhibit cancer pain. Therefore, P2X may be another potential pharmacological target for the treatment of cancer pain.